2009
DOI: 10.1029/2009gc002458
|View full text |Cite
|
Sign up to set email alerts
|

Midcrustal low‐velocity layer beneath the central Himalaya and southern Tibet revealed by ambient noise array tomography

Abstract: [1] Ambient noise tomography has been becoming an important tool to image the shallow lithospheric structure of the Earth. Using 2 months of ambient noise data from 20 stations of the Himalayan Nepal Tibet Seismic Experiment, we investigate the upper and middle crustal structure in the central Himalaya and southern Tibet. About 120 interstation Rayleigh wave empirical Green's functions with sufficient signal-tonoise ratio are obtained and used for group velocity dispersion analysis in the period range 6-25 s u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 73 publications
(107 reference statements)
7
48
0
1
Order By: Relevance
“…7) throughout the mid-crust in most of Tibet has also been observed in a number of previous studies (e.g. Cotte et al 1999;Rapine et al 2003;Caldwell et al 2009;Guo et al 2009;Li et al 2009;Yang et al 2012;Agius & Lebedev 2014;Jiang et al 2014;Li et al 2014;Sun et al 2014;Bao et al 2015;Deng et al 2015;Gilligan et al 2015). Our results have high resolution across the entire Tibetan Plateau and the Pamirs, whereas many previous studies have mainly focused on more restricted geographical regions.…”
Section: P O S S I B L E C Au S E O F T H E L O W V E L O C I T Y L Amentioning
confidence: 42%
“…7) throughout the mid-crust in most of Tibet has also been observed in a number of previous studies (e.g. Cotte et al 1999;Rapine et al 2003;Caldwell et al 2009;Guo et al 2009;Li et al 2009;Yang et al 2012;Agius & Lebedev 2014;Jiang et al 2014;Li et al 2014;Sun et al 2014;Bao et al 2015;Deng et al 2015;Gilligan et al 2015). Our results have high resolution across the entire Tibetan Plateau and the Pamirs, whereas many previous studies have mainly focused on more restricted geographical regions.…”
Section: P O S S I B L E C Au S E O F T H E L O W V E L O C I T Y L Amentioning
confidence: 42%
“…The mid-to-lower LVZ beneath the SongpanGanzi terrane is similar to the LVZs observed beneath other parts of the plateau, such as the eastern, central, and southern Tibetan plateau. Geophysical studies using different methods also found high-electrical conductivity, high-temperature, partial melting, low-velocity, and low-strength zones in the mid-to-lower crust beneath the plateau (e.g., Clark et al, 2005;Royden et al, 2008;Yao et al, 2008;Guo et al, 2009;Li et al, 2009;Bai et al, 2010;Yang et al, 2012). The crustal flow model suggested that the weak mid-to-lower crustal materials beneath the Tibetan plateau probably contributed to the elevated topography and crustal thickening of the Tibetan plateau (Clark and Royden, 2000;Royden et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The collision between the Indian and Eurasian plates not only has caused significant elevation and highly deformed orogenic belts within the Tibetan plateau, but also impacts remote areas such as eastern China and the Baikal rift to the north (Molnar and Tapponnier, 1975;Tapponnier and Molnar, 1977;Bendick and Flesch, 2007). Many studies have been performed in the Tibetan plateau, but most of the geophysical studies of the Tibetan crust and mantle structure to date have focused on the southern Kind et al, 1996;Nelson et al, 1996;Huang et al, 2000;Wei et al, 2001;Wang et al, 2003;Unsworth et al, 2005;Yao et al, 2008;Guo et al, 2009), central (Owens and Zandt, 1997;Kind et al, 2002;Tilmann et al, 2003), and eastern Tibetan plateau , with the primary objectives of understanding the continental collision process and the intrusion of the crustal and mantle materials from the Indian plate into the Eurasian plate. In comparison to other parts of the plateau, fewer seismic investigations have been done in the northeastern Tibetan plateau (e.g., Wittlinger et al, 1996;Zhu and Helmberger, 1998;Vergne et al, 2002Vergne et al, , 2003Karplus et al, 2011Karplus et al, , 2013Yue et al, 2012), which either are localized along linear profiles or focused on the velocity discontinuity structure.…”
Section: Introductionmentioning
confidence: 99%
“…Typically the real data are dominated by one type of noise generation source, e.g., ocean waves, and the resulting cross-correlation is dominated by a narrow range of frequencies. Recent works on noise cross-correlation have indicated the potential of cross-correlating long signal time windows between stations to yield an empirical Green's function PICOZZI et al, 2009;YANG et al, 2007YANG et al, , 2010YANG and RITZWOLLER, 2008a, b;STACHNIK et al, 2008;NISHIDA et al, 2008;MOSCHETTI et al, 2007;MARZORATI and BINDI, 2008;MA et al, 2008;LIN et al, 2007;BENSEN et al, 2007BENSEN et al, , 2008BRZAK et al, 2009;TSAI, 2009;GUO et al, 2009;LI et al, 2009LI et al, , 2010YAO and VAN DER HILST, 2009, CHOI et al, 2009CUPILLARD and CAPDEVILLE, 2010;CRISTIANO et al, 2010).…”
Section: Noise Cross-correlation Methodsmentioning
confidence: 99%